Предмет: Алгебра,
автор: Enot322
Помогите пожалуйста. Заранее спасибо!
Приложения:
Ответы
Автор ответа:
0
4√27 = √27*16= √432
3√48=√48*9 = √432 ⇒ √432 = √432 ⇒ 4√27 = 3√48
или так
4√27 = 4√9*3 =4*3√3= 12√3
3√48= 3√16*3= 3*4√3= 12√3 ⇒ 12√3 =12√3 ⇒ 4√27 = 3√48
3√48=√48*9 = √432 ⇒ √432 = √432 ⇒ 4√27 = 3√48
или так
4√27 = 4√9*3 =4*3√3= 12√3
3√48= 3√16*3= 3*4√3= 12√3 ⇒ 12√3 =12√3 ⇒ 4√27 = 3√48
Автор ответа:
0
Спасибо большое!
Автор ответа:
0
))
Похожие вопросы
Предмет: Английский язык,
автор: Vikasss88
Предмет: Алгебра,
автор: rabovadara41
Предмет: Английский язык,
автор: pqpqqpoq
Предмет: Математика,
автор: разумчик1